Effects of a Bt-based insecticide on the functional response ofCeraeochrysa cinctapreying onPlutella xylostella - Oliveira Pimenta, Isabela Cristina de (2020)
Plutella xylostella, is the main pest infestingBrassicacrops, and products based onBacillus thuringiensis(Bt) are frequently used in strategies for its biocontrol. The present study aimed to evaluate whether a Bt-based bioinsecticide affects the predation behavior ofCeraeochrysa cinctawhen preying onP. xylostella. Three larval instars of the predator and the eggs and second-instar larvae of the moth were used, with the prey either untreated or treated with a Bt-based product (Xentari (R)). Results showed that, the first larval instar ofC. cinctapresented a type II functional response when preying upon untreated eggs, and a type III response when preying upon Bt-treated eggs, while the second and third instars presented type II and III responses, respectively, in both situations. The predator's first and third larval instars presented a type II functional response when preying upon untreated larvae and a type III response when preying upon Bt-treated larvae. However, the predator's second-instar larvae showed a type II response in both treatments. The results obtained allowed us to conclude that the Bt-based insecticide tested affects the predation behavior of the first-instar larvae ofC. cinctaon eggs and of both the first- and third-instar larvae of this predator onP. xylostellalarvae.